NILAI-NILAI BUDAYA TRADISI LISAN DALAM PERTUNJUKAN JIKI HADARA PADA PERNIKAHAN MASYARAKAT BIMA: KAJIAN ANTROPOLOGI LINGUISTIK - Muh. Sha'ad Bawazzir; Johan Mahyudi; Aswandikari Aswandikari (Universitas Islam Negeri Mataram, 2023)
This research is a qualitative description research that produces descriptions in from written or spoken words of the people and the observer behavior. This study aims to describe the form of performance, indexicality, and participation. Oral traditional cultur values and inheritance systems in the Jiki Hadara performance, indexicality, and inheritance systems in the Jiki Hadara performance at the wedding of the Bima people with a linguistic anthropological perspective. The theory used in this study is the theory of linguistic anthropology from Duranti. The data collection was carried out using the observation method, the proficient method, and the transcription method. Data analysis using qualitative methods consisting of data reduction, data presentation and drawing conclusions. The result of this study indicate that the Jiki Hadara performance at the wedding of the Bima community in the Tumpu Village, Bolo sub-district,has forms of performance, indexicality, and participation. Besides that, there are also traditional values in this research as well as an inheritance system that can provide an understanding in maintaining a traditional culture. This research is expected to be material for discussion for all groups, especially for cultural and scientific activists, especially in the field of linguistic anthropology.